MORPHOMETRICS OF JUVENILE WHITE SHRIMP IN SANTOS (SP, BRAZIL) - AN ATLANTIC STRESSED ESTUARY - Felippe Veneziani ABBATEPAULO; Sergio Luiz dos Santos TUTUI; Acacio Ribeiro Gomes TOMÁS (Boletim do Instituto de Pesca)
Shrimps are one of the world’s most valuable fishing resources, with the Penaeidae family having the greatest economic importance. In the southwest Atlantic the white shrimp Litopenaeus schmitti plays an important socioeconomic role for small-scale fisheries, and juveniles are targeted as live bait for recreational fisheries. This study was carried out monthly along two periods (May/2009‑January/2010 and March/2011-March/2015) at Santos estuary and aimed to investigate the relationship between morphometric and sex of the early development stages of Litopenaeus schmitti. A total of 6,978 individuals were caught and measured, with no differences (p >0.1) between sexes shown regarding total length or weight. Differences between males and females were found for Total length (TL) x Carapace length (CL) and TL x Total weight (TW) and negative allometries (b<3) were found for all relationships. The results indicate that morphometric differences among sexes seem to be more associated with total length, suggesting that TL could be a more appropriate body measurement to compare specimens of L. schmitti, at least when the analysis includes juveniles. The presence of L. schmitti specimens all year long inside the estuary reinforces the idea of a continuous reproductive cycle with peak periods. Both information comes to fulfill part of the lack of knowledge regarding this species estuarine phases.